2022
DOI: 10.1007/s44202-022-00020-y
|View full text |Cite
|
Sign up to set email alerts
|

Acceptance and Fear of Artificial Intelligence: associations with personality in a German and a Chinese sample

Abstract: Understanding individual differences in attitudes towards Artificial Intelligence (AI) is of importance, among others in system development. Against this background, we sought to investigate associations between personality and attitudes towards AI. Relations were investigated in samples from two countries—Germany and China—to find potentially replicable, cross-culturally applicable associations. In German (N = 367, n = 137 men) and Chinese (N = 879; n = 220 men) online surveys, participants completed items on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
26
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 38 publications
4
26
1
Order By: Relevance
“…In line with Sindermann et al (2021), general trust in AI as assessed by the ATAI scale is robustly linked to trusting products with in-built AI, indicating a high external validity of the construct. Although previous observations suggest that the ATAI scales are associated with individual variations in behavioral tendencies such as neuroticism (Sindermann et al, 2022), the present study did not observe a relationship between trust in humans and trust in AI in general or trust in AI products, respectively. Further examination of structural brain data revealed that variations in trust in AI were not significantly associated with individual variations in brain structure.…”
Section: Discussioncontrasting
confidence: 99%
“…In line with Sindermann et al (2021), general trust in AI as assessed by the ATAI scale is robustly linked to trusting products with in-built AI, indicating a high external validity of the construct. Although previous observations suggest that the ATAI scales are associated with individual variations in behavioral tendencies such as neuroticism (Sindermann et al, 2022), the present study did not observe a relationship between trust in humans and trust in AI in general or trust in AI products, respectively. Further examination of structural brain data revealed that variations in trust in AI were not significantly associated with individual variations in brain structure.…”
Section: Discussioncontrasting
confidence: 99%
“…Fear and anxiety are much studied in psychology, hence research on AI anxiety is often conducted by psychologists in the context of different personality traits [109], fear of loneliness, of drone use, of autonomous vehicles, and of being unemployed, all of it being elevated with media exposure to science fiction [110][111][112][113].…”
Section: Fear Of Ai (Ai Anxiety)mentioning
confidence: 99%
“…First, examining the impact of psychological factors shows that individuals' attitude towards AI is infuenced by their personality traits [73]. In [89], it was shown that fear and distrust towards AI are associated with neuroticism, while openness and agreeableness are related to acceptance of AI. Additionally, personal values have been shown to impact artists' attitude towards AI co-creation in creative tasks.…”
Section: Background and Related Work 21 Factors Infuencing Perception...mentioning
confidence: 99%
“…Broadly, several factors are known to impact people's acceptance of AI. Individuals' personality traits can induce fear and distrust towards AI [73,89]. Additionally, cultural factors [74] such as fear of unemployment due to AI deployment [49,63]), portrayals of AI in popular culture [5,6], degree of familiarity with modern AI technologies [76], and expectations of privacy in interaction [62] all infuence perceptions of AI.…”
Section: Introductionmentioning
confidence: 99%